TINJAUAN YURIDIS TERHADAP PELAKU USAHA PEREDARAN PAKAIAN BEKAS IMPOR DI KOTA BAUBAU - Zamrud, Wa Ode; Amalia, Ayu Rizki (Jurnal Ilmu Hukum Kanturuna Wolio, 2024)
The purpose of writing this thesis is to answer how the regulation of the circulation of imported used clothing (Thrift) in Baubau City and what are the efforts made by the Baubau City Trade Office in handling the trade in imported used clothing (Thrift) in Baubau City. The results showed that the legal arrangements made by the Baubau City Trade Office were only limited to curbing. This is because used clothing that enters the territory of Baubau City does not yet have a special arrangement and is still traded freely, from that Baubau City requires legal arrangements on circulation to deal with the used clothing trade, although used clothing provides many business opportunities it cannot be denied if used clothing is prohibited from being traded. Efforts made by the Department of Trade in dealing with the Imported Used Clothing Trade in Baubau City include conducting socialization and raids on the circulation of used clothing in markets and ports, so that if the circulation continues to occur, the Department of Industry and Trade of Baubau City cooperates with the police to withdraw goods and destroy goods.